The role of haemoglobin A2 testing in the diagnosis of thalassaemias and related haemoglobinopathies. Issue 1 (22nd December 2008) - Mosca, A; Paleari, R; Ivaldi, G; Galanello, R; Giordano, P C
Abstract : The increase in haemoglobin (Hb)A2 level is the most significant parameter in the identification of β thalassaemia carriers. However, in some cases the level of HbA2 is not typically elevated and some difficulties may arise in making the diagnosis. For these reasons the quantification of HbA2 has to be performed with great accuracy and the results must be interpreted together with other haematological and biochemical evidence. The present document includes comments on the need for accuracy and standardisation, and on the interpretation of the HbA2 value, reviewing the most crucial aspects related to this test. A practical flow-chart is presented to summarise the significance of HbA2 estimation in different thalassaemia syndromes and related haemoglobinopathies.